Fiber Coupled High Power Nd:YAG Laser for Nondestructive Laser Cleaning - Xiaolei Wang; Xinqiang Ma; Yuan Ren; Jingwen Wang; Wei Cheng (Photonics, 2023)
In this study, a fiber coupled high power side-pumped Nd:YAG laser system for laser cleaning is presented. Based on the two-rod structure and two stages amplifiers, the maximum average output power of 783 W with corresponding pulse energy of 52 mJ at 15 kHz has been achieved. The fiber coupling efficiencies after the master oscillator, one stage amplifier and two stages amplifiers reach to 99%, 98.3% and 94%, respectively. A laser cleaning machine prototype composed of the master oscillator and one stage amplifier with an average output power of greater than 500 W has been developed and achieved better nondestructive cleaning effect for thermal control coating removal compared with commercial fiber laser cleaning machines. This study provides a new method for developing high power laser sources for nondestructive laser cleaning equipment.